A low-cost dual output switch mode power supply (SMPS) for laptop - Palaniappan Balathandayutham (2010)
All electronic circuits need a supply of power to operate. Often a battery, even a solar cell, will suffice for the low power consumption units. However, for most applications the power consumption is that an electronics power supply unit must be used. Over the past 10 years, there have been significant changes in the design of the power supplies. The most important of these has been the widespread changes from linear power supply to those operate on a switching basis. This project presents a theoretical background, design and realization progress of a low cost dual output switch mode power supply (SMPS) for laptop that will incorporates a switching regulator in order to provide the required DC output voltage with rating of 60W. It has a fly back topology and utilizes one power switch to facilitate the transfer of energy from the input to output. In this switched-mode power supply switches a power transistor between saturation and cutoff with a variable duty cycle whose average is the desired output voltage. It switches at a much-higher frequency 40 kHz than that of the AC line, which means that the transformer that it feeds can be much smaller than one connected directly to the line/mains. Switching creates a rectangular waveform that typically goes to the primary of the transformer; typically secondary feed rectifiers and filter capacitors to provide various DC outputs with low ripple. In addition, analyzed the input voltage fluctuation effect and the consequent input PF variation of SMPS and implemented additional circuits that needed to improve both consequences.